2015
DOI: 10.1152/ajprenal.00290.2015
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA landscape in hypoxic and inflammatory renal epithelial injury

Abstract: Long noncoding RNAs (lncRNAs) are emerging as key species-specific regulators of cellular and disease processes. To identify potential lncRNAs relevant to acute and chronic renal epithelial injury, we performed unbiased whole transcriptome profiling of human proximal tubular epithelial cells (PTECs) in hypoxic and inflammatory conditions. RNA sequencing revealed that the protein-coding and noncoding transcriptomic landscape differed between hypoxia-stimulated and cytokine-stimulated human PTECs. Hypoxia- and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 64 publications
3
65
0
Order By: Relevance
“…This finding was further confirmed in TECs treated with plasma of critically ill sepsis AKI patients (J. Lin et al, 2015). A Q-PCR-based diseaserelated lncRNA array identifies that among 83 disease-related lncRNAs, 28 lncRNAs are upregulated and 55 lncRNAs are downregulated in TEC under hypoxia , others also detect 5,361 upregulated lncRNAs and 5,928 downregulated lncRNAs in the septic AKI group compared with control (Chun-Mei, Qin-Min, Shu-Ming, & Xiang-Yang, 2016).…”
Section: Role Of Lncrnas In Akimentioning
confidence: 75%
See 1 more Smart Citation
“…This finding was further confirmed in TECs treated with plasma of critically ill sepsis AKI patients (J. Lin et al, 2015). A Q-PCR-based diseaserelated lncRNA array identifies that among 83 disease-related lncRNAs, 28 lncRNAs are upregulated and 55 lncRNAs are downregulated in TEC under hypoxia , others also detect 5,361 upregulated lncRNAs and 5,928 downregulated lncRNAs in the septic AKI group compared with control (Chun-Mei, Qin-Min, Shu-Ming, & Xiang-Yang, 2016).…”
Section: Role Of Lncrnas In Akimentioning
confidence: 75%
“…J. Lin et al (2015) identified the noncoding transcriptomic landscape of human TECs in hypoxia and inflammation conditions, where MIR210HG and linc-ATP13A4-8 were induced by hypoxia while MIR210HG and linc-KIAA1737-2 were induced by inflammatory cytokines. This finding was further confirmed in TECs treated with plasma of critically ill sepsis AKI patients (J.…”
Section: Role Of Lncrnas In Akimentioning
confidence: 99%
“…In an unbiased profiling study to identify lncRNAs that are modulated during renal tubular epithelial cell responses to hypoxia and inflammatory stimuli, Lin et al [89] identified several differentially expressed lncRNAs. Of these, modulation of MIR210HG, linc-ATP13A4-8, and linc-KIAA1737-2 abundance was confirmed in human tubular epithelial cells isolated from transplant biopsies as well as in epithelial cells exposed to plasma from patients with sepsis [89].…”
Section: Long Noncoding Rnas In Renal Diseasementioning
confidence: 99%
“…Of these, modulation of MIR210HG, linc-ATP13A4-8, and linc-KIAA1737-2 abundance was confirmed in human tubular epithelial cells isolated from transplant biopsies as well as in epithelial cells exposed to plasma from patients with sepsis [89]. Although a specific role for these lncRNAs has not been attributed, pathway and loci analyses were indicative of their involvement in biological pathways related to cellular stress and inflammatory response.…”
Section: Long Noncoding Rnas In Renal Diseasementioning
confidence: 99%
“…77 Hypoxia-and inflammation-modulated lncRNAs have also emerged as key species-specific regulators of cellular and disease processes. 79 For example, RNA-seq of human proximal tubular epithelial cells under hypoxic and inflammatory conditions to identify potential lncRNAs relevant to acute and chronic renal epithelial injury revealed changes in the expression of three lncRNAs under hypoxic and inflammatory conditions. In the same study, the loci of these lncRNAs were determined and associated epigenetic marks were defined.…”
Section: Epigenetic Findings In Kidney Diseasementioning
confidence: 99%